2013
DOI: 10.1002/adsc.201300077
|View full text |Cite
|
Sign up to set email alerts
|

Cinchona Alkaloid‐Derived Thiourea‐Catalyzed Diastereo‐ and Enantioselective [3+2] Cycloaddition Reaction of Isocyanoacetates to Isatins: A Facile Access to Optically Active Spirooxindole Oxazolines

Abstract: An efficient diastereo-and enantioselective [3+2] cycloaddition reaction of a-aryl isocyanoacetates to isatins catalyzed by a quinine-derived bifunctional amine-thiourea-bearing sulfonamide as multiple hydrogen-bonding donor catalyst has been investigated. The corresponding adducts, which bear a spirocyclic quaternary stereocenter at the C-3 position of the oxindole, were obtained in good yields (51-95%), high diastereoselectivities (up to > 20:1 dr) and good to excellent enantioselectivities (up to 97% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Catalyst 35 was the best of a series tested in this application ( Figure 34). [65] In this case the isocyanate formed the basis of a second ring fused in a spiro fashion and under optimised conditions a good level of stereocontrol. Multiple hydrogen bonding interactions are again likely to be responsible for control of absolute stereochemistry here, and better results were obtained with some of the substituted substrates.…”
Section: Use Of N-thiourea Tsdpen Derivatives In Asymmetric Catalysismentioning
confidence: 99%
“…Catalyst 35 was the best of a series tested in this application ( Figure 34). [65] In this case the isocyanate formed the basis of a second ring fused in a spiro fashion and under optimised conditions a good level of stereocontrol. Multiple hydrogen bonding interactions are again likely to be responsible for control of absolute stereochemistry here, and better results were obtained with some of the substituted substrates.…”
Section: Use Of N-thiourea Tsdpen Derivatives In Asymmetric Catalysismentioning
confidence: 99%
“…gaining further attention in the following years as catalysts for several sorts of transformations. [49][50][51] Furthermore, Cinchona-derived thiourea catalysts successfully promoted cycloaddition reactions such as [4 + 2], [3 + 2] and their formal versions, being well suited, for instance for the synthesis of 2H-pyran-2,5-diones, 52 3,3′-pyrrolidinyl spirooxindoles, 53,54 1,3-dioxolanes, 55 α-aryl isocyanoacetates and isatins, 56 as well as 2-oxazolidinones. 57…”
Section: Catalysis Science and Technology Minireviewmentioning
confidence: 99%
“…In 2013, Shi, Zhao and co-workers developed a highly enantioselective [3 + 2] cycloaddition reaction of α-aryl isocyanoacetates and isatins towards optically active spirooxindole oxazolines catalyzed by Cinchona alkaloid derived bifunctional amine-thiourea-bearing sulfonamide 17 (Scheme 18). 56 Although, the electronic and steric properties of the isatin derivatives had significant influence on the reaction, the authors could furnish all products with moderate to excellent yields and enantioselectivities. A limitation of the cycloaddition reaction was observed in attempts employing an orthosubstituted aryl group (R 2 = 2-MeC 6 H 4 ) or an α-isopropyl isocyanoacetate (R 2 = i-Pr), respectively, which showed no conversion.…”
Section: [3 + 2] and Formal [3 + 2] Cycloadditionsmentioning
confidence: 99%
“…Zhao et al reported the use of a quinine-derived bifunctional amine-thiourea-bearing sulfonamide ( Figure 44) as a multiple hydrogen-bonding donor catalyst in the reactions of isatins with α-substituted isocyanoacetates. 78 Several isatin derivatives with diverse electronic and steric environments underwent formal [3+2]-cycloaddition, affording optically active spirooxindole oxazolines. The reactions occurred most efficiently in diethyl ether, affording products with good yields (51%-95%), high diastereoselectivity (up to >20:1 DR), and good-to-excellent enantioselectivity (80%-97% EE).…”
Section: Application Of Cinchona-derived Catalysts In [3+2]-cycloaddimentioning
confidence: 99%